2013
DOI: 10.1021/es3045955
|View full text |Cite
|
Sign up to set email alerts
|

Template-Free Synthesis of Nanostructured CdxZn1–xS with Tunable Band Structure for H2 Production and Organic Dye Degradation Using Solar Light

Abstract: We have demonstrated a template-free large-scale synthesis of nanostructured Cd(x)Zn(1-x)S by a simple and a low-temperature solid-state method. Cadmium oxide, zinc oxide, and thiourea in various concentration ratios are homogenized at moderate temperature to obtain nanostructured Cd(x)Zn(1-x)S. We have also demonstrated that phase purity of the sample can be controlled with a simple adjustment of the amount of Zn content and nanocrystalline Cd(x)Zn(1-x)S(x = 0.5 and 0.9) of the hexagonal phase with 6-8 nm siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…As expected, the main peak positions of SnS 2− x Se x alloys gradually shift toward lower angles with increasing Se content (Fig. 1b), indicating the increase of lattice constants and formation of solid solution rather than the mechanical mixture of two pure phases2728. The continuous peak shifting (lattice expanding) of ternary alloys might rule out the phase separation or separated nucleation of SnS 2 or SnSe 2 nanomaterials2930.…”
Section: Resultssupporting
confidence: 67%
“…As expected, the main peak positions of SnS 2− x Se x alloys gradually shift toward lower angles with increasing Se content (Fig. 1b), indicating the increase of lattice constants and formation of solid solution rather than the mechanical mixture of two pure phases2728. The continuous peak shifting (lattice expanding) of ternary alloys might rule out the phase separation or separated nucleation of SnS 2 or SnSe 2 nanomaterials2930.…”
Section: Resultssupporting
confidence: 67%
“…3. Earlier reports have reviewed a nanostructured film with Cd 0.9 Zn 0.1 S hexagonal and Cd 0.5 Zn 0.5 S polytypic or cubic form existing in the hexagonal phase, while Cd 0.1 Zn 0.9 S shows the cubic phase [1,2,43].…”
Section: Resultsmentioning
confidence: 99%
“…As the Zn content in Zn x Cd 1 À x S increases, its conduction and valence bands shift to more negative and positive positions, respectively; this increases the bang-gap width and effectively decreases recombination of photogenerated electron-hole pairs [4]. Garaje et al [14] have shown a decreasing of photocatalytic degradation efficiency of organic dye from 98% to 78% although the band gap of Cd x Zn 1 À x S only has a small increase from 2.48 to 2.85 eV when the value of x in Cd x Zn 1 À x S increases from 0.1 to 0.5. Macías-Sánchez et al [15] have reported that the band gap increases from 2.15 to 2.23 eV, which causes the H 2 evolution amounts increasing from 520 μmol to 962 μmol, when the value of x in Cd x Zn 1 À x S/S15 increases from 0.1 to 0.2.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic activities of Zn x Cd 1 À x S are higher than that of CdS [14,15]. However, the reported photocatalytic activities are still low, and it is important to improve their photocatalytic properties by designing semiconductor composites to further suppress electron-hole pair recombination.…”
Section: Introductionmentioning
confidence: 99%